PTU-036 Endoscopic Management of Malignant Gastric Outlet Obstruction: Results from a Newly Created Regional Cancer Service. (4th June 2013) - Ismail, D; Deacon, J; Macfarlane, B; Morris, D L; Fullard, M; Sargeant, I; Evans, J; Leahy, A
Abstract : Introduction: Malignant gastric outlet obstruction can be a distressing medical condition leading to considerable morbidity with a well recognised poor prognosis. Previous studies (mostly outside of the UK) have shown that endoscopic insertion of a duodenal stent can alleviate the obstructive symptoms to good effect (1–3). In 2009, we set up a regional service for duodenal stent insertion with an aim to replicate these results across a UK upper gastro-intestinal cancer network (catchment area 1.4 million). Methods: A retrospective analysis was performed in patients who had an endoscopically placed duodenal stent for inoperable cancer causing mechanical gastric outlet obstruction. We reviewed hospital/endoscopy electronic records regarding patient demographics, length of hospital stay after the procedure, endoscopy re-intervention and survival. Results: Between July 2009 and November 2012 a total of 27 patients underwent duodenal stent (uncovered WallFlex®, Boston Scientific) insertion. 15 were men, mean age of 70.6 years (range 27–86). 23/27 (85%) patients were discharged home after the procedure, 2 were transferred to a hospice and 2 died in hospital. The average length of hospital stay after the procedure was 5.7 days (range 0–25). Endoscopy re-intervention was performed in 2 patients for stent occlusion requiring further stent insertion. 22 patients have been followed until death with a mean survival period of 12.5 weeks (range 1–34). 5 patients remain alive at the time of abstract submission. Conclusion: Duodenal stent insertion offered a good palliative option in most of our patients. Our patient outcomes compared favourably to previous published studies. Disclosure of Interest: None Declared References: ASGE Technology Committee. The role of endoscopy in gastroduodenal obstruction and gastroparesis. Gastrointest Endosc 2011; 74(1):13–21. Sasaki T, Isayama H, Maetani I et al. Japanese multicenter estimation of wallflex duodenal stent for unresectable malignant gastric outlet obstruction Dig Endosc 2013 25(1):1–6. Costamagna G, Tringali A, Spicak J et al. Treatment of malignant gastroduodenal obstruction with a nitinol self-expanding metal stent: an international prospective multicentre registry. Dig Liver Dis 2012 44(1):37–43.